Теорія і практика трансформаційних процесів економіки України в умовах сучасних викликів - Скорик, Г. І.; Барінов, В. В. (Видавництво Львівської політехніки, 2015)
Проаналізовано поточні тенденції розвитку економіки України, показано взаємозв’язок економічної кризи та економічної політики в Україні із кризою економічної науки; підкреслено, що результати реформування економіки України, масове зубожіння населення, безробіття багато у чому зумовлені ігноруванням реального стану економіки країни, сліпим копіюванням рекомендацій західних експертів і недооцінкою державного регулювання. Звернено увагу на те, що, незважаючи на певні переваги неоліберального підходу щодо розбудови економіки, він призвів до багатьох негативних соціально-економічних наслідків як у світі, так і в Україні. Підкреслено, що на зміну концепцій, що мінімізують роль держави в економіці, повинно прийти розуміння комплементарності ринку і держави. The current tendencies of economic growth in Ukraine are analysed with the correlation of the economic crisis and economic policy in Ukraine with economics crisis being showed; it was emphasized that the outcomes of Ukraine’s economy restructuring are in many respects predetermined by the neglect of the real state of the national economy, by blind imitation of western experts’ recommendations and the underestimation of the state regulation. The implementation of liberalism policy, taken blindly and without restrictions in Ukraine proved to bring about not the prosperity but mass impoverishment of population, unemployment, which forced a considerable share of population to leave the country in search for better life and causes the deepening of inequality in incomes and wealth. It was emphasized that regardless of some benefits of neoliberal approach concerning economic development, it caused а variety of negative social-economic circumstances as in the world, so in Ukraine. It was accentuated, that only those development strategy and economic policy can be effective that come from proper economic theory, based on which better future can be built. Its main features are recession from any dogmatism, from blind conformity to any ideology or policy line; toolkit flexibility, opened for all-round search for preventive tools, used for specific situation. The supporters of liberal economy must admit the necessity of extensive government intervention in economy functioning, particularly in crisis environment. Government regulation of economic life should have systematic manner, and the reforms should be implemented complexly in all directions of economic policy, in sectors of economy, regions and population. In order to overcome the crisis effects it’s mostly important that the applied measures meet the standards of law and legality, equal rights and responsibility of economic agents. It was pointed out, that government regulation should secure the maximum of economic freedom of enterprises on the basis of simplification and liberalization of legislation, bureaucratic procedure, improvement and simplification of tax system and possibly the liquidation of customs duties on imports of technologies, patents, modern equipment, which will attract the investment in the country and facilitate the positive dynamics of production in Ukraine.
Theory and practice transformation process Ukraine economy under current challenges
Keywords: державне регулювання; трансформаційний процес; неолібералізм; криза економічної науки; компліментарність ринку і держави; соціальний лібералізм; government regulation; transformation process; neoliberalism; economics crisis; complementarity of market and state; social liberalism